1996
DOI: 10.1103/physrevd.53.5966
|View full text |Cite
|
Sign up to set email alerts
|

Barbero's Hamiltonian derived from a generalized Hilbert-Palatini action

Abstract: Barbero recently suggested a modification of Ashtekar's choice of canonical variables for general relativity. Although leading to a more complicated Hamiltonian constraint this modified version, in which the configuration variable still is a connection, has the advantage of being real. In this article we derive Barbero's Hamiltonian formulation from an action, which can be considered as a generalization of the ordinary Hilbert-Palatini action.Comment: 6 page

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
855
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 538 publications
(874 citation statements)
references
References 8 publications
16
855
0
3
Order By: Relevance
“…It is remarkable that the second class constraints (12) and (14) don't depend on β that proves consistency of the constraints in different formulations. One can calculate…”
Section: Covariant Canonical Formulationmentioning
confidence: 97%
See 1 more Smart Citation
“…It is remarkable that the second class constraints (12) and (14) don't depend on β that proves consistency of the constraints in different formulations. One can calculate…”
Section: Covariant Canonical Formulationmentioning
confidence: 97%
“…In the work [12] Holst has shown that in the "time" gauge this action reproduces Barbero's formulation [8] and the parameter β plays the role of the Immirzi parameter. Our aim is to investigate the action (1) without imposing any gauge fixing.…”
Section: Generalized Hilbert-palatini Actionmentioning
confidence: 99%
“…The third term, widely known as the Holst term [20], is not topological. When written down in EinsteinCartan language, it bears a close kinship to the Einstein-Hilbert term in the action.…”
Section: Cp Violationmentioning
confidence: 99%
“…The coefficients at both are even functions of 1/γ, which means that they effectively arise via even powers of P -and T -odd term in (1). Besides, the coefficient at V 2 is proportional to α 2 , i.e.…”
mentioning
confidence: 99%
“…This explains rather unexpected symmetry properties of the induced effective 4-fermion interaction.As has been demonstrated in [1], the gravitational action can be written asHere I, J = 0, 1, 2, 3 are internal Lorentz indices, µ, ν = 0, 1, 2, 3 are space-time indices; e I µ is the tetrad field, e is its determinant, and e µ I is the object inverse to e I µ ; the curvature tensor isω IJ µ is the connection. As to the so-called Immirzi parameter γ, the common belief is that it does not enter equations of motion since it appears as a factor at the term that vanishes on mass shell.…”
mentioning
confidence: 99%